A principal components analysis: how pneumatization and edentulism contribute to maxillary atrophy. (13th September 2016) - Wagner, F; Dvorak, G; Nemec, S; Pietschmann, P; Figl, M; Seemann, R
Abstract : Objective: The aim of this retrospective cohort study was to investigate the role of sinus pneumatization and residual ridge resorption in maxillary bone loss in 400 computed tomography (CT) scans. Materials and Methods: In 200 dentate and 200 edentulous patients, both sinuses were analysed using CT scans. The image analysis sequence consisted of manual placement of 24 reference points, followed by automated segmentation and final manual refinement. Finally, a principal components analysis was performed. Results: A total of 788 sinuses were included into the analysis. The edentulous group (98 female: 67.77 ± 11.28 years, 99 male: 65.22 ± 9.87) was significantly older than the group with teeth (99 female: 46.89 ± 16.77 years, 96 male: 49.74 ± 16.2). Female and male patients did not differ regarding age. The alveolar height differed significantly between the groups (edentulous: 7.1 ± 4.3 mm, with teeth: 9.7 ± 4.1 mm), but not between gender (female: 8.3 ± 4.4 mm, male: 8.5 ± 4.4 mm). Principal components analysis was able to explain 90% of the variation in sinus morphology. Conclusions: Prolonged edentulism in the maxillary molar region leads to centripetal and to minor degrees centrifugal ridge resorption. Minor pneumatization occurs in the sinus walls, but the sinus depth underlies the anatomical variation independent of dentition.